PENGARUH PENGASAMAN PADA SPESIASI CU(II) DALAM SISTEM ASAM HUMAT-AIR - Sunarsih, Sri; Santosa, Sri Juari; -, Mudasir (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
The influences of acidify and humic acid (HA) weight on Cu(II) speciation in humic acid-water system has been studied. The HA was extracted from peatsoil in Siantan, Pontianak, West Kalimantan. The Cu(II) solution was made from Cu(SO)4.s H2O crystal of E.Merck for analytical grade. The acidify effect test carried out with 50 mL of Cu(II) solution in 100 ppm concentration then varied their pH level at 4, 5 ,6, 7 and 8. To each solution added with 30 mg of HA, be interacted in 1 hour, and then settled in 24 hour to be equilibrium. The same procedure were done to prepare the solutions for determining the effect of HA weight on Cu(II) speciation. The weight of HA varied at 20, 40, 60, 80 and 120 mg with pH solution 5,0. The concentration of total Cu and hydrated Cu(II) were determined using Atomic Absorption Spectrophotometer and Ionic Selective Electrode (ISE), respectively. Based on measurement of total Cu and hydrated Cu known that if the initial pH of solution higher, the absorption of Cu to HA became higher too. The fraction that was not absorbed distributed as hydrated Cu and Cu-AH complex that their concentration was in equilibrium at pH value of 5,0. The result of pH measurement at the equilibrium, the value of Ksp Cu(OH)2 and calculation of OH- indicated that there were no deposition of Cu(OH)2 formed. The measurement also indicated that if the more weight of HA applied on the interaction, the absorption to Cu became higher. The fraction that was not adsorbed increasingly as Cu-AH complex.